2021
DOI: 10.3390/en14175302
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Protocol for Thermal Performance of District Heating Pipes in Operation. Part 2: Estimation of Present Thermal Conductivity in Aged Pipe Insulation

Abstract: Buried and operating district heating (DH) pipes are exposed to thermal degradation of their polyurethane (PUR) insulation over time, and their status is hard to assess without excavation. By using DH pipe valves in manholes as measurement points during a shutdown with an ensuing cooling period, non-destructive assessments can be performed. This study compares new improved field measurements with numerical simulations of the temperature decline in drainage valves and shutdown valves. The drainage valve measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…During the experimental studies, the places of coolant leakage into the ground were identified together with the sections of heat pipelines with an unsatisfactory state of thermal insulation materials. A similar problem Energies 2022, 15, 2784 2 of 11 was addressed by researchers from the Chalmers University of Technology comparing the results of numerical modelling and measurements using non-destructive testing [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…During the experimental studies, the places of coolant leakage into the ground were identified together with the sections of heat pipelines with an unsatisfactory state of thermal insulation materials. A similar problem Energies 2022, 15, 2784 2 of 11 was addressed by researchers from the Chalmers University of Technology comparing the results of numerical modelling and measurements using non-destructive testing [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was conducted whilst considering the perspectives of both the cogeneration plant and the end user. A very different subject was explored by Liden et al in a two-part article [5,6]. They addressed the problem related to the thermal degradation of DH pipe insulation over time, which is highly difficult to quantify without excavation.…”
mentioning
confidence: 99%
“…As a next step, a diagnostic protocol was developed and established for application to DH pipes in operation [6]. In particular, the choice of the drainage valves as measurement points has proven to be the most appropriate for capturing the temperature decline in the DH pipe during the above-mentioned cooling period.…”
mentioning
confidence: 99%